A qualitative study of resilience among transgender women living with HIV in response to stigma in healthcare. Issue 8 (2nd August 2020) - Lacombe-Duncan, Ashley; Logie, Carmen H.; Newman, Peter A.; Bauer, Greta R.; Kazemi, Mina
ABSTRACT: Stigma in healthcare is a pervasive adversity experienced by transgender (trans) women living with HIV (WLWH). Resilience is described as individual and collective processes of navigating and overcoming adversity. This qualitative study sought to explore resilience exhibited by trans WLWH in response to stigma in healthcare. Semi-structured, individual interviews were conducted in 2017–2018 with a purposive sample of trans WLWH ( n  = 11) participating in a community-based cohort study. Framework analysis was used to identify key themes, patterns within themes between participants, and patterns across themes among participants. Three overarching themes were identified. (1) Resilient responses to stigma in healthcare . Participants exhibited resilient personality traits and processes of resistance and transformation in response to stigma. (2) Motivations, benefits, and consequences of responding . Participants experienced self and altruistic driven motivations. Benefits included increased self-worth, economic resources, and leverage for better healthcare treatment, and reduced internalized stigma and isolation. Negative consequences included defensive provider reactions, being further stereotyped, and decreased physical and mental health. (3) Recommendations for systemic change . Participants recommended trans inclusion in service delivery, development, and management, as well as increased provider education. Providers can leverage trans WLWH's personal and collective strengths while working in solidarity to reduce stigma in healthcare settings.